PERBANDINGAN MANAJEMEN LABA DAN PENGHINDARAN PAJAK SEBELUM DAN DI MASA PANDEMI COVID-19 Studi Kasus: Perusahaan Sektor Barang Konsumen Non-Primer Tahun 2017–2020 - Cahyani, Pramesti Regista (Media Akuntansi dan Perpajakan Indonesia, 2023)
This study was conducted to compare earnings management and tax avoidance before the pandemic and during the Covid-19 pandemic in non-primary consumer goods sector companies. The existence of a pandemic causes economic conditions to become unstable. People are becoming more conservative in spending their money on primary needs and medicines so that non-primary goods have the potential to experience a decrease in income. Therefore, there is a potential loophole for these companies to take earnings management and tax avoidance actions to maintain company liquidity. In this study, earnings management is measured by a specific accrual model, namely by comparing the accrual of working capital with sales/ income. Meanwhile, tax avoidance is measured by the CETR ratio. The object of this research is non-primary consumer goods sector companies listed on the Indonesia Stock Exchange. The data used uses secondary data in the 2017–2020 financial statements. The test was carried out using a different test method or paired-sample t test which was normally distributed. The results of this study are that there is a significant difference in earnings management before and during the pandemic, while in tax avoidance before and during the pandemic there is no significant difference.